Critical Analysis of Emotional Intelligence From Two Perspectives: Goleman's Theory and the Guidance of the Quran - Lativa, Lativa; Ratnasari, Dwi (Lembaga Yasin AlSys, 2025)
Emotional intelligence (EQ) has emerged as a critical dimension of human functioning, often exerting a more substantial influence on personal and professional success than intellectual intelligence (IQ), as emphasized in the work of Daniel Goleman. EQ encompasses the ability to identify, regulate, and express one’s own emotions, as well as to perceive and respond appropriately to the emotions of others. This study explores the concept of emotional intelligence through the lens of Goleman's theoretical framework and investigates its correspondence with ethical and spiritual values found in the Qur’an. Employing a qualitative-descriptive approach, the research focuses on three core components of EQ as outlined by Goleman, self-motivation, empathy, and social skills, and analyzes these constructs in relation to Qur’anic teachings. The findings reveal that the Qur’an embodies principles of emotional intelligence through narratives and moral exhortations, such as persistence in adversity (istiqamah), compassion toward others, emotional restraint, and respectful interpersonal communication. Prophetic stories and ethical injunctions provide illustrative models of emotionally intelligent behavior aligned with spiritual development. This study demonstrates that integrating modern psychological theories with Qur’anic values offers a rich and culturally grounded framework for character education and personal growth. It also underscores the potential of Islamic teachings to contribute meaningfully to contemporary discourses on emotional intelligence and moral development.